Community structure and diversity of tree species in a lowland dipterocarp forest of Sungai Lalang Forest Reserve, Selangor, Malaysia - FAEZAH PARDI; RIDAHATI RAMBEY; HASYA HANNANI RUZIMAN (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Pardi F, Rambey R, Ruziman HH. 2026. Community structure and diversity of tree species in a lowland dipterocarp forest of Sungai Lalang Forest Reserve, Selangor, Malaysia. Biodiversitas 27 (1): d270107. https://doi.org/10.13057/biodiv/d270107. Lowland dipterocarp forests in Peninsular Malaysia are biodiversity hotspots that play crucial roles in carbon storage but are increasingly threatened by logging, land conversion, and recreational pressures. Quantitative data on their community structure remain limited, particularly for Sungai Lalang Forest Reserve (SLFR), Selangor. To fill this gap, this study aimed to assess floristic composition and diversity, and estimate biomass and carbon stock in SLFR. In doing so, ten plots covering three hectares were established to enumerate trees with a diameter at breast height ≥5 cm. The tree community comprised a wide representation of families and genera, with Fabaceae emerging as the most species-rich, while Elateriospermum tapos (Euphorbiaceae) was identified as the dominant species. Diversity was moderate, but species evenness was low, reflecting uneven distribution across taxa. Despite this, the forest stored a significant carbon, with an estimated 304.86 t/ha, indicating its primary role as an important carbon sink. Importantly, seven threatened species were recorded, including Hopea auriculata and Palaquium burckii (Critically Endangered), Anisoptera costata and Neobalanocarpus heimii (Endangered), Ctenolophon parvifolius, Pentace macrophylla and Shorea inappendiculata (Vulnerable). Their occurrence urges the conservation importance of SLFR as a reservoir of dipterocarp diversity and a refuge for threatened taxa. Management strategies should prioritize stricter regulation of recreational activities, targeted enrichment planting, and the protection of threatened species. By integrating biodiversity conservation with climate mitigation goals, sustainable management of SLFR will directly contribute to the objectives of Sustainable Development Goal 15.